Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem Based Learning (PBL) Berbantuan Canva pada Pembelajaran Pendidikan Pancasila di Kelas IV SDN 04 Gunung Tuleh Kabupaten Pasaman Barat - Rahmadia, Yesi; Mansurdin, Mansurdin; Engreini, Syofianti; Putera, Rafhi Febryan (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to describe the improvement of student learning outcomes using the Problem Based Learning (PBL) model assisted by Canva in Civics Education learning. The type of research used is classroom action research (CAR) employing two approaches: qualitative and quantitative. This research was conducted in two cycles with a research procedure consisting of planning, implementation, observation, and reflection. Data collection techniques included tests and non-tests. Descriptive quantitative analysis was used to analyze the results. The subjects of this study are 36 students in grade IV consisting of 14 males and 22 females. The results of the study showed that the teaching module of the first cycle was obtained on average 88.75%, increasing in the second cycle to 97.5%. The results of the implementation of teacher aspect learning in the first cycle were obtained on average 85.75%, increasing in the second cycle to 96.42%. The results of the implementation of learning aspects of students in the first cycle were obtained on average 85.75%, increasing in the second cycle to 96.42%. The learning outcomes of students in the first cycle were obtained on average 78.08, increasing in the second cycle to 92.54. Thus, it can be concluded that the Canva assisted Problem Based Learning (PBL) model can improve student learning outcomes in Pancasila Education learning in elementary schools.